Etnomatematika Urban: Kajian Kontekstual Matematika pada Sistem Transjakarta - JELITA AULIA RABBANI; DEVI SEPTIANI AHMAD; ASYIFATU ZAHRA; MAIFALINDA FATRA (Fakultas Ilmu Pendidikan Universitas Muhammadiyah Jakarta, 2025)
The study of urban Ethnomathematics within the context of modern culture, focusing on the TransJakarta transportation system, requires in-depth attention. This research aims to analyze the mathematical concepts internalized in TransJakarta’s design, operation, and user experience to advance contextual learning (CTL and RME). The study utilizes a qualitative approach involving direct observation of physical artifacts (CSW Station, buses) and operations, in-depth interviews with users, and documentation, with strategic locations such as Lebak Bulus and CSW Stations. The results show that infrastructure design represents geometrical concepts (circles, prisms), while the route network can be modeled using Directed Graph Theory () with CSW serving as the central node of highest connectivity (degree 6). Furthermore, queuing patterns and passenger waiting time estimation indicate the intuitive use of concepts of proportion and probability by the public. Pedagogically, these findings affirm that mathematics is a living cultural construct, not merely an abstract concept, and is highly relevant for use as a real-world learning context to enhance student engagement and critical understanding. The novelty of this research lies in the comprehensive integration of ethnomathematics with a modern Bus Rapid Transit system. Keyword: Ethnomathematics, TransJakarta, Graph Theory, Geometry, and Urban Culture